"Capgras" Delusions Involving Belongings, Not People, and Evolving Visual Hallucinations Associated with Occipital Lobe Seizures. (7th March 2018) - Lilly, Brandon; Maynard, Erika; Melvin, Kelly; Holroyd, Suzanne
Abstract : Capgras syndrome is characterized by the delusional belief that a familiar person has been replaced by a visually similar imposter or replica. Rarely, the delusional focus may be objects rather than people. Numerous etiologies have been described for Capgras to include seizures. Similarly, visual hallucinations, both simple and complex, can occur secondary to seizure activity. We present, to our knowledge, the first reported case of visual hallucinations and Capgras delusions for objects that developed secondary to new onset occipital lobe epilepsy. We then discuss the possible underlying neurologic mechanisms responsible for the symptomatology.